2015
DOI: 10.1007/s00344-015-9492-y
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Profile in Ovaries of Mandarin Varieties with Differing Reproductive Behaviour

Abstract: The endogenous levels of 13 gibberellins (GAs), three cytokinins (CKs), abscisic acid (ABA), indole-3-acetic acid (IAA) and jasmonic acid (JA) were analyzed in naturally pollinated ovaries of three mandarin cultivars selected for their different capacity to produce seeds and their differing parthenocarpic ability. The varieties compared were Murcott (pollen self-compatible, highly seeded), Moncada (self-incompatible, moderately seeded), and Moncalina (pollen sterile, seedless), obtained from Moncada by bud c-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Interestingly, we found that exogenous MT induced parthenocarpy in pear, whereas exogenous IAA could not ( Figure 1 ). Previous studies have shown that ovaries synthesize large amounts of IAA post-pollination to promote fruit development ( Bermejo et al, 2015 ). In our study, IAA content as well as the number of seed cell layers in the ovary did not increase after MT treatment, and IAA content declined after pollination compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that exogenous MT induced parthenocarpy in pear, whereas exogenous IAA could not ( Figure 1 ). Previous studies have shown that ovaries synthesize large amounts of IAA post-pollination to promote fruit development ( Bermejo et al, 2015 ). In our study, IAA content as well as the number of seed cell layers in the ovary did not increase after MT treatment, and IAA content declined after pollination compared with the control.…”
Section: Discussionmentioning
confidence: 99%
“…[26]. GA is commercially recommended for the Citrus hybrids exhibiting 'weak parthenocarpy' and 'insufficient cross-pollination,' aiming to enhance the 'fruit set' [27]. Sequential applications of GA3 mitigate flowering and sprouting intensity in 'Montenegrina' mandarin trees during the spring [28].…”
Section: Gibberellic Acid (Ga)mentioning
confidence: 99%
“…Despite several positive traits, some unwanted traits like the excessive seededness (15-30 seeds/fruit) greatly hinders consumer's acceptability, as crushed seeds cause bitterness in the extracted juice. Seedlessness is of paramount importance in citrus breeding and has been attempted by several workers using conventional and non-conventional breeding techniques (Bermejo et al, 2015) [6] . Induced mutagenesis has scientific and commercial interests to improve the plant growth, yield and quality characteristics of commercially important plants.…”
Section: Introductionmentioning
confidence: 99%